2013
DOI: 10.1103/physrevlett.111.137002
|View full text |Cite
|
Sign up to set email alerts
|

Charge Qubit Coupled to an Intense Microwave Electromagnetic Field in a Superconducting Nb Device: Evidence for Photon-Assisted Quasiparticle Tunneling

Abstract: We study a superconducting charge qubit coupled to an intensive electromagnetic field and probe changes in the resonance frequency of the formed dressed states. At large driving strengths, exceeding the qubit energy-level splitting, this reveals the well known Landau-Zener-Stückelberg (LZS) interference structure of a longitudinally driven two-level system. For even stronger drives we observe a significant change in the LZS pattern and contrast. We attribute this to photon-assisted quasiparticle tunneling in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The resonators are instrumental for the whole field of circuit quantum electrodynamics (c-QED) for having dramatically reduced microwave mode volume, as compared to bulk cavities, and accordingly increased coupling to engineered q-bits and spins. 7,8 Among the two generic planar resonator types, microstrip and coplanar, both are ubiquitous in industrial applications, 9,10 while only the latter is dominant in superconducting designs. This is because, in pursuit to squeeze the mode volume, the central line-to-ground gap in a typical coplanar resonator for c-QED applications is only a few microns wide.…”
mentioning
confidence: 99%
“…The resonators are instrumental for the whole field of circuit quantum electrodynamics (c-QED) for having dramatically reduced microwave mode volume, as compared to bulk cavities, and accordingly increased coupling to engineered q-bits and spins. 7,8 Among the two generic planar resonator types, microstrip and coplanar, both are ubiquitous in industrial applications, 9,10 while only the latter is dominant in superconducting designs. This is because, in pursuit to squeeze the mode volume, the central line-to-ground gap in a typical coplanar resonator for c-QED applications is only a few microns wide.…”
mentioning
confidence: 99%
“…As a superconducting circuit is cooled well below its critical temperature, the quasiparticle density via BCS theory is expected to be exponentially suppressed, but a number of experimental groups have reported higher-than-expected values in a wide variety of systems [7][8][9][10]. Although the reasons for the enhanced quasiparticle population or the mechanism behind quasiparticle generation are not fully understood, their presence has a number of adverse effects on the qubit performance, causing relaxation [11][12][13][14][15][16], dephasing [17][18][19], excess excited-state population [20], temporal variations in qubit parameters [21][22][23][24], and are predicted to be a major obstacle for realizing Majorana qubits in semiconductor nanowires [25]. Our results provide an in situ technique for removing quasiparticles, especially in conjunction with recent experiments showing that vortices in superconducting electrodes can act as quasiparticles traps, thus keeping the quasiparticles away from the Josephson junctions where they may contribute to qubit relaxation [22,[26][27][28].…”
mentioning
confidence: 99%
“…In particular, we demonstrate that in a specific experimentally feasible parameter regime, squeezing at a high photon number can be achieved even in the presence of maximum gate-charge disorder. It follows that this device is robust against strong thermal noise in the DC-voltage bias 34 and nonequilibrium quasiparticles in the CPTs [35][36][37][38] .…”
Section: Introductionmentioning
confidence: 87%
“…In the limit of maximum disorder, it is also a rough model for (non-equilibrium) quasiparticle poisoning in the CPTs, which can be triggered in the high-intensity limit by quasiparticle tunneling due to direct multi-photon absorption 37 . For conventional lasers it has been shown that the lasing state is robust against disorder in the atomic detuning, the coupling strength to the resonator, and the pumping strength 28 .…”
Section: Effect Of Charge Disordermentioning
confidence: 99%